2018
DOI: 10.1111/jnp.12148
|View full text |Cite
|
Sign up to set email alerts
|

Words fail: Lesion‐symptom mapping of errors of omission in post‐stroke aphasia

Abstract: Impaired object naming is a core deficit in post-stroke aphasia, which can manifest as errors of commission - producing an incorrect word or a non-word - or as errors of omission - failing to attempt to name the object. Detailed behavioural, computational, and neurological investigations of errors of commission have played a key role in the development of neurocognitive models of word production. In contrast, the neurocognitive basis of omission errors is radically underspecified despite being a prevalent phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…This method is an extension of support vector machines (Cortes and Vapnik, 1995). SVR is able to model continuous variables and has been successfully implemented in SVR-based lesion symptom mapping (SVR-LSM) to map lesion-behaviour relationships with high resolution on a whole-brain voxel-level (Zhang et al, 2014;Mirman et al, 2015b;Fama et al, 2017;Griffis et al, 2017;Ghaleh et al, 2018;Chen et al, 2018;Sperber et al, in press). Most importantly, SVR-LSM was validated in a set of simulation studies for simple brain networks (Zhang et al, 2014).…”
Section: Multivariate Lesion Behaviour Mapping By Svr-lsmmentioning
confidence: 99%
“…This method is an extension of support vector machines (Cortes and Vapnik, 1995). SVR is able to model continuous variables and has been successfully implemented in SVR-based lesion symptom mapping (SVR-LSM) to map lesion-behaviour relationships with high resolution on a whole-brain voxel-level (Zhang et al, 2014;Mirman et al, 2015b;Fama et al, 2017;Griffis et al, 2017;Ghaleh et al, 2018;Chen et al, 2018;Sperber et al, in press). Most importantly, SVR-LSM was validated in a set of simulation studies for simple brain networks (Zhang et al, 2014).…”
Section: Multivariate Lesion Behaviour Mapping By Svr-lsmmentioning
confidence: 99%
“…As recently highlighted, ‘the same error can be caused by more than one type of deficit’ (Halai et al ., ). In the case of omissions, different reasons have been enumerated, ranging from insufficient semantic activation of lexical representations to difficulties at the low‐level visual input (see Chen et al ., ; Tochadse et al ., ). Infering the neural correlates of a function by studying dysfunction following brain damage or inactivation, the so‐called lesion‐deficit approach (Genon, Reid, Langner, Amunts, & Eickhoff, ), has proven to be a successful strategy.…”
Section: Introductionmentioning
confidence: 98%
“…Infering the neural correlates of a function by studying dysfunction following brain damage or inactivation, the so‐called lesion‐deficit approach (Genon, Reid, Langner, Amunts, & Eickhoff, ), has proven to be a successful strategy. In this sense, convergent data from neuropsychological studies with patients with primary progressive aphasia (Mesulam et al ., ; Wilson, Dehollain, Ferrieux, Christensen, & Teichmann, ; Wilson et al ., ); stroke‐related aphasia (Chen et al ., ; Halai et al ., ); anatomo‐electro‐clinical correlations of patterns of ictal aphasia in temporal lobe epilepsy (TLE) using stereoelectroencephalography (Trebuchon et al ., ); and brain (Pobric, Jefferies, & Ralph, ), and intraoperative stimulation studies (Miozzo, Williams, McKhann, & Hamberger, ), have suggested an association of omission errors with anterior temporal lobe (ATL) dysfunction. Nonetheless, other studies have indicated that omission errors can be also related to damage to regions in the posterior temporal cortex (Antonucci, Beeson, Labiner, & Rapcsak, ; Baldo, Arévalo, Patterson, & Dronkers, ; Cloutman et al ., ; Herbet et al ., ; Trebuchon‐Da Fonseca et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To sum up, we investigated the contribution of control mechanisms during semantic retrieval and selection in healthy adults and adults with stroke-induced lesions using a word-picture matching task and computational modelling (HDDM). With that, we add to an existing body of literature that combines computational modelling with a lesion mapping approach, which provides a promising avenue towards formalizing brain-behavior relations (Chen, Middleton, & Mirman, 2018;Dell, Martin, & Schwartz, 2007;Hoffman, McClelland, & Lambon Ralph, 2018).…”
Section: Introductionmentioning
confidence: 99%